جدلية الزمن في المنتج المعماري - محمد يسار عابدين; زياد المهنا (Tishreen University, 2019)
The relationship between architecture and time appears clearly in many faces, starting with the fact that the architectural product is a temporal, cultural witness documents the history and expresses the cultural values, the cultural concepts, and the economic situation and explains the scientific and technical level. The existing architectural works represent a temporal series of the real physical history; considering that time is an apparent founder component through the architectural product`s procedures formula whether by design, execution, operation, evaluation, or historical criticism. The research intends to discuss the temporal dialectic within the architectural product by asking questions about the architect`s vision of time, and framing the temporal correlations in architecture as a philosophy, mechanism and output; in order to setup a vision of the temporal link to architecture by introducing a set of definitions, determine  the concept of the temporal architectural and draw the relationships between them; with an accentuation of the continued necessity to this philosophical argument to expand and unify the knowledge base in architectural criticism. The research consists of an introduction of conceptual time and introduce the definition of architectural time flow. Then, the research classified the hyperlink time structures in architectural product by an original philosophical style, after determine the concept of temporal building. Finally, the research concludes a series of important results in its dialectical topic. تظهر علاقة العمارة بالزمن بجلاء في أوجه عديدة بدءاً من أنَّ المنتج المعماري شاهد زمني حضاري يوثق التاريخ ويعبِّر عن القيم والمفاهيم الثقافية والحالة الاقتصادية ويفسر المستوى العلمي والتقني.  فالأعمال المعمارية القائمة تمثل سلسلة زمنية من التاريخ المادي الحقيقي؛ وعلى اعتبار أن الزمن عنصر مؤسس ظاهر في إجراءات صياغة المنتج المعماري سواء بالتصميم أو التنفيذ أو التشغيل أو التقييم والنقد والتأريخ. يعمد البحث إلى مناقشة الجدلية الزمنية في المنتج المعماري من خلال طرح تساؤلات حول نظرة المعمار للزمن، وتأطير الارتباطات الزمنية في العمارة كفلسفة وآلية وناتج؛ بهدف وضع رؤية لأوجه ارتباط الزمن بالعمارة عبر طرح مجموعة من التعاريف وتحديد المفاهيم الخاصة بالزمن المعماري ورسم العلاقة فيما بينهما؛ مع التأكيد على ضرورة استمرار هذا الجدال الفلسفي لتوسيع وتوحيد القاعدة المعرفية في النقد المعماري. ويتألف البحث من مدخل تعريفي لمفاهيم الزمن والزمان، وطرح تعريف التدفق الزمني المعماري. يأتي بعدها البحث لإجراء تصنيف تشعبي لأنواع الزمن في المنتج المعماري بأسلوب فلسفي أصيل، وبعد تحديد مفهوم الأبنية الزمنية، يختم البحث بمجموعة من النتائج الهامة في موضوع هذه الجدلية.